Associated intraabdominal malformations of right-sided congenital diaphragmatic hernia: A rare anomaly and review - Gabija Pikturnaitė; Austėja Račytė; Rūta Vilija Dagilytė; Arūnas Strumila; Gilvydas Verkauskas (Elsevier, 2022)
There is scarce literature on associated anomalies of right-sided congenital diaphragmatic hernias (CDH). The purpose of this study was to expand the presentation of a unique clinical experience by a literature review. Only six articles of a right-sided CDH linked to non-cardiac anomalies with complicated diagnostic and treatment scenarios were found related to ours. To the best of our knowledge, it is the first presented case of a right-sided CDH with multiple intestinal atresias and an intrathoracic right kidney. This case alerts physicians to take all examination details into account to avoid delaying CDH diagnosis. Most importantly, it gives valuable insight into possible associated anomalies of right-sided congenital diaphragmatic hernias and may benefit future embryological or genetic studies.